Os efeitos da globalização no modelo nórdico de estado de bem-estar social: o caso da Suécia - Reolon, Felipe Barboza (Universidade do Vale do Rio dos Sinos, 2021)
The welfare state’s origins can be dated back to Germany in the 19th century, based on the ideals of social protection implemented by Bismarck. The Nordic Model, consecutively, adapting this system to the Scandinavian principles of equality and universalism, attained greater notoriety in the 20th century with the adoption of Keynes' contributions to the international economy by the international community. At the end of the 20th century and beginning of the 21st century, the globalization phenomenon intensified in an unprecedented manner due to the reduction of geographical and communication barriers amidst the creation of new technologies. This work aims, therefore, to understand how the Swedish welfare state is affected by the globalization process, from an International Political Economy approach, assimilating the role of the national state in the international context of the 21st century. As a result, it can be seen that globalization has had effects on the Swedish domestic system in the political, economic, and social spheres.
Keywords: Estado de bem-estar social; Economia Política Internacional; Globalização; Suécia; Welfare State; International Political Economy; Globalization; Sweden